A preliminary checklist of the freshwater snails of Sabah (Malaysian Borneo) deposited in the BORNEENSIS collection, Universiti Malaysia Sabah - Ng, Ting Hui; Jasrul Dulipat; Foon, Junn Kitt; Manuel Lopes-Lima; Liew, Thor Seng; Alexandra Zieritz (Pensoft Publishers, 2017)
Sabah, a Malaysian state at the north-eastern tip of Borneo, is situated in one of the Earth’s biodiversity hotspots yet its freshwater gastropod diversity remains poorly known. An annotated checklist of the freshwater gastropods is presented, based on specimens deposited in the BORNEENSIS collection of the Institute for Tropical Biology and Conservation at Universiti Malaysia Sabah, Malaysia. A KMZ file is also provided, which acts as a repository of digital images and complete collection data of all examined material, so that it can be shared and adapted to facilitate future research.